Invertebrate Biosecurity Challenges in High-Productivity Grassland: The New Zealand Example - Goldson, Stephen L.; Barratt, Barbara I. P.; Armstrong, Karen F. (Frontiers in Plant Science, 2016)
To protect productive grasslands from pests and diseases, effective pre- and at-border planning and interventions are necessary. Biosecurity failure inevitably requires particularly expensive and difficult eradication, or long term and often quite ineffective management strategies. Early intervention is more likely for sectors where there is public and political interest in plants of immediate economic and/or social value and where associated pests are typically located above-ground on host plantings of limited distribution. Here, biosecurity surveillance and responses can be readily designed. In contrast, pastures comprising plants of low inherent unit value that create little, if any, aesthetic interest. Yet, given the vast extent of pasture in New Zealand and the value of the associated industries, these plants are of immense economic importance. Compounding this is the invasibility of New Zealand’s pastoral’s ecosystems through a lack of biotic resistance to incursion and invasion. Further, given the sheer area of pasture, intervention options are limited because of costs per unit area and the potential for pollution if pesticides are used. Biosecurity risk for pastoral products differs from, say, fruit imports where at least part of an invasive pathway can be recognised and risks assessed. The ability to do this via pastoral sector pathways is much reduced, since risk organisms more frequently arrive via hitchhiker pathways which are diffuse and varied. Further, pasture pests within grassland ecosystems are typically cryptic, often with subterranean larval stages. Such characteristics make detection and response particularly difficult. The consequences of this threatens to add to the already-increasing stressors of production intensification and climate change. This review explores the unique challenges for pasture biosecurity, and what may be done to confront existing difficulties. While there is no silver bullet, opportunities for improving pasture biosecurity may include increased and informed vigilance by farmers, pheromone traps and resistant plants to slow invasion. Increasingly, there is also the potential for more use of advanced population dispersal models and surveillance strategies including unmanned aerial vehicles, as well as emerging techniques to determine invasive pest genomes and their geographical origins.